Pregnancy in women with congenital heart disease - van Hagen, Iris M.; Roos-Hesselink, Jolien W. (SA Heart Journal, 2017)
Due to the enormous improvements in the treatment of children with congenital heart disease, an increasing number of patients reach adulthood nowadays. To achieve the aim of excellent care concerning pregnancy in this patient population, a pro-active discussion of pregnancy with all women in this patient population is essential. Several risk stratifi cation models have been developed in order to identify high risk pregnancies and better inform patients about these risks. Counselling and dedicated care are needed to optimise both maternal and fetal outcomes. Better access to health care systems contributes to further improvements in mortality and morbidity. Furthermore a well-developed, multidisciplinary plan for each individual patient concerning pregnancy, delivery and follow-up is essential.